Texas Toys and Games - Abernethy, Francis Edward; Project Muse. (University of North Texas Press, 1997)
Given by the Descendants of Austin's Old Three Hundred.
Description based on print version record.
Keywords: Toys; Toy making; Games; Folklore; Toy making; Games; Toy making -- History; Folklore -- Texas -- History; Games -- Texas -- History; Toys -- Texas -- History; Texas; History; Electronic books